2016
DOI: 10.1021/acs.jpcb.6b05761
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization and Isomerism Effects on Two-Photon Absorption of Tetraphenylethene Derivatives and Molecular Design for Two-Photon Absorption Materials

Abstract: The two-photon absorption (TPA) properties of a new tetraphenylethene derivative and its covalent dimers have been calculated employing the density functional response theory. It is found that linear arrangement of branches can give rise to a cooperative TPA behavior. Partial planarity and linear arrangement are the possible reasons for the observed aggregation-induced TPA enhancement. On the basis of the model molecule, we have designed a series of tetraphenylethene derivatives which differ by donor moieties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Our previous work has shown that the B3LYP functional calculations can give reasonable TPA properties which are consistent with the trend of experimental observations. [24][25][26][27][28] The use of the pseudo potential basis sets could probably provide better numerical results, but we believe that the overall picture would not change.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work has shown that the B3LYP functional calculations can give reasonable TPA properties which are consistent with the trend of experimental observations. [24][25][26][27][28] The use of the pseudo potential basis sets could probably provide better numerical results, but we believe that the overall picture would not change.…”
Section: Methodsmentioning
confidence: 99%
“…At the same computational level, the optical properties of different compounds can be compared accurately. [24][25][26][27][28] In this work, we choose a di-2-picolylamine (DPA)-based Zn 2+ ion TP probe as a model molecule. It has been reported that this probe undergoes significant increase of the TPA cross section by the Zn 2+ coordination.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has shown that the B3LYP functional calculations can give reasonable TPA properties which are consistent with the trend of experimental observations. [19][20][21][25][26][27][28][29] The use of bigger basis sets could probably provide better numerical results, but we believe that the overall picture would not change.…”
Section: Methodsmentioning
confidence: 99%
“…Although isomerism is quite a common phenomenon in chemistry, the effects of isomerism on TPA properties of organic molecules have seldom been discussed in the literature. [23,24] In our previous researches, [25][26][27][28][29] we investigated the influences of isomerism on TPA properties for a series of TPA active molecules. For a probe in solution at room temperature, various isomers of free and bound fluorophores are possible and produce specific spectral features.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 In our previous work, 30 we successfully designed a series of ICT-based TP fluorescent Zn 2+ sensors through using several electron donors and acceptors to increase both TPA and fluorescence quantum yield. Apart from electron donors and acceptors, isomerism also plays an important role in TPA [34][35][36][37] and fluorescence. 38,39 It is well known that the fluorescence quantum yield (0.13) of phenanthrene is lower than that (0.30) of anthracene.…”
Section: Introductionmentioning
confidence: 99%